Electromechanical delay of the hamstrings following semitendinosus tendon autografts in return to competition athletes - Morris, N.; Jordan, M. J.; Heard, M.; Herzog , W. (European Journal of Applied Physiology, 2021)
Purpose: Knee flexor electromechanical delay (EMD) has been proposed as a contributing factor to non-contact anterior cruciate ligament (ACL) injury risk and the semitendinosus (ST) autograft technique has been shown to impair knee flexor torque at large angles of knee flexion. The purpose of this study was to analyse the effects of ACL reconstruction (ACLR) using the ST tendon autograft technique on knee flexor EMD across the knee flexion range of motion, in athletes who had returned to competition. Methods: Athletes with ACLR (n = 8 females, n = 3 males, 1.7 ± 0.5 years post-surgery) and non-injured control athletes (n = 6 females, n = 4 males) performed rapid maximal voluntary contractions of isometric knee flexion and extension at 30°, 50°, 70°, 90°,and 105° of knee flexion. Electrical activity of the ST, biceps femoris (BF), vastus lateralis, and vastus medialis was recorded using surface electromyography. Results: No change in EMD for the knee flexors or extensors was observed across joint angles. Greater EMD was found only for the BF in the ACLR limb of injured athletes compared to the contralateral limb (P < 0.05). In post-hoc analysis, evidence of ST tendon regrowth was noted for only 2/11 athletes. Conclusion: While the EMD-joint angle relationship appeared to be unaffected by ST tendon harvest for ACLR, the absence of ST tendon regrowth should be considered. Despite return to competition, greater BF EMD was found, which may impair knee joint stabilization capacity by delaying the transfer time of muscle tension to the tibia after ST autograft.